Lone Rangers no more: archival cooperation in transition. Issue 1 (January 2018) - Farrugia, Charles J.
Abstract : Archival cooperation has changed over the last few decades. Building on the author's experience of over 27 years in the archive sector, and on his study and lecturing experiences overseas, the paper focuses on collaboration between archival institutions and sister professions and information management entities in a number of different countries. It explains how archives of small underfunded countries, whose collections nevertheless hold international treasures, can empower their resources through international collaboration. Networks built around specialised themes such as a photographic archives, audio-visual material and the protection of the collective memories of diasporic communities living far from their homeland, are highlighted. Examples of successful new models of collaboration emphasize how archival networking across international borders turns the archivist from a "Lone Ranger" to a member of a large international community, steered by the ICA, guided by ethical and professional principles, and making best use of technology to overcome traditional boundaries.